Characteristics and Antioxidant Activity of Nanoparticles Chitosan Roselle (Hibiscus sabdariffa) - Utari, Retno Diyah; Saputra, Budi; Kristiana, Randi; Yunita, Tiani; Kusumaningtyas, Valentina Adimurti; Jasmansyah, Jasmansyah (Jurnal Kartika Kimia, 2022)
Roselle (Hibiscus sabdariffa) contains flavonoids with antioxidant activity. The present study aimed to examine the characteristics and antioxidant activity index (AAI) of roselle extract (RE) after being modified into nanoparticles chitosan of roselle (NCR). Phytochemical screening indicated that roselle extract contains flavonoids, saponins, tannins and steroid/triterpenoids compounds. The NCR was prepared using a bottom-to-up method from a cross-link reaction between chitosan and tripolyphosphate. The ratio of RE:Chitosan:Tripolyphosphate was 2:1:0.1. NCR characterization showed 464.6 nm of a particle size, 0.849 of a polydispersion index and -6.0 mV of a zeta potential. Antioxidant activity was measured by utilizing the DPPH method (2,2-diphenyl-1-picrylhydrazyl), with a UV-Vis spectrophotometer at a wavelength of 515 nm. IC50 data were analyzed using the One Way Annova test with a confidence level of 95%. Results showed that NCR had an IC50 value of 22.577 ppm (AAI:2.217), which is classified as a very strong antioxidant. The IC50 value of the RE was 77.610 ppm (AAI:0.644), which is categorized as a moderate antioxidant. The results of this study reveal that the modification of roselle extract (RE) into nanoparticles chitosan of roselle (NCR) was proven to enhance the AAI (p<0.05).